Pricing water quality in China : valuation using happiness data - Lim, Jamie Si Ying (Nanyang Technological University, 2020)
Water quality is a key policy challenge for China, even with the increased implementation of various policies targeting it in recent years. To ensure that the most efficient policies are implemented, accurate economic valuation for the costs of water pollutants are required to conduct cost-benefit analysis. This paper addresses two key existing literature gaps, firstly, in usage of the happiness approach to provide a value for water quality, and secondly, the provision of values for individual water quality indicators in China. Data from the China Family Panel Studies (CFPS) was used in tandem with other data sources to create multivariate regression models so as to study the relationship between happiness and pH, dissolved oxygen (DO), potassium permanganate (KMnO4), and ammonia nitrogen (NH3-N) respectively, as well as to obtain willingness to pay (WTP) values for each. Heterogenous effects and values for different groups were also modelled. Even though the robustness checks and WTP values indicate that there may be omitted variable bias or other underlying issues that may limit the direct application of these results for policy applications, the results provide suggestive evidence for the relationship between happiness and pH, DO, KMnO4, and NH3-N in China and possible avenues for future research.